'You get some very archaic ideas of what teaching is … ': primary school teachers' perceptions of the barriers to physically active lessons. Issue 3 (3rd April 2019) - Quarmby, Thomas; Daly-Smith, Andy; Kime, Nicky
ABSTRACT: Physically active lessons present a key paradigm shift in educational practice. However, little is known about the barriers to implementing physically active lessons. To address this, 31 practising primary teachers (23 = female ) from 9 primary schools across West Yorkshire, England, were engaged in focus group interviews. Drawing on the socio-ecological model, findings revealed that barriers influencing the implementation of physically active lessons are multifaceted. Teacher's confidence and competence, concerns over classroom space, preparation time and resources, coupled with the wider school culture that is influenced by governors and parents, reinforce a didactic approach and act as barriers to physically active lessons.